Platformized Cultural Marketing in Art, Heritage, and Creative Industries: A Systematic Literature Review of Social Media Research - Catharina Aprilia Hellyani; Nanang Suryadi; Raditha Dwi Vata Hapsari (LPPM Universitas KH A. Wahab Hasbullah, 2026)
Social media has rapidly transformed marketing practices in the arts, heritage, and creative industries. It has shifted from a secondary promotional channel into a strategic infrastructure that shapes branding, audience engagement, visibility, and value creation in platform-mediated environments. However, existing research remains fragmented across cultural sectors, digital platforms, and disciplinary traditions. This study systematically reviews contemporary research on social media and cultural marketing using the PRISMA framework. Data were collected from the Scopus database through a structured Boolean search. From 291 initial records, 94 English-language journal articles published between 2020 and 2026 were selected for final analysis after applying eligibility criteria related to publication year, language, document type, source type, publication stage, subject area, and thematic relevance. The thematic synthesis identifies four main findings. First, social media has reconfigured cultural branding from one-way promotion into platform-adaptive communication based on visual identity, storytelling, and strategic visibility. Second, audience engagement is increasingly understood as a multidimensional process involving participation, co-creation, emotional connection, and relational value. Third, platformization reshapes discoverability and legitimacy through algorithmic visibility, platform metrics, and content-format conventions. Fourth, emerging technologies, including artificial intelligence, analytics, immersive media, and virtual influencers, expand innovation opportunities while raising ethical and managerial concerns related to authenticity, transparency, and institutional capability. This review contributes to cultural marketing and creative economy research by conceptualizing social media as a platformized environment where branding, engagement, visibility, and technological readiness interact to shape cultural value creation. It also identifies gaps in longitudinal, comparative, cross-cultural, and mixed-method studies.